Population genomics and pathotypic evaluation of the bacterial leaf blight pathogen of rice reveals rapid evolutionary dynamics of a plant pathogen - Song, Zhiwei; Zheng, Jinshui; Zhao, Yancun; Yin, Jiakang; Zheng, Dehong; Hu, Huifeng; Liu, Hongxia; Sun, Ming; Ruan, Lifang; Liu, Fengquan (Frontiers in Cellular and Infection Microbiology, 2023)
Xanthomonas oryzae pv. oryzae (Xoo) causes bacterial blight disease, which reduces crop yield by up to 50% in rice production. Despite its substantial threat on food production worldwide, knowledge about its population structure, virulence diversity, and their relationship is limited. We used whole-genome sequencing to explore the diversity and evolution of Xoo during the past 30 years in the main rice-planting areas of China. Six separate lineages were revealed by phylogenomic analysis, with CX-5 and CX-6 predominating in the population for decades. The recent sporadic outbreaks were caused by Xoo derived from these lineages, especially the two major ones. The lineage and sub-lineage distributions of isolates were strongly correlated with their geographical origin, which was found to be mainly determined by the planting of the two major rice subspecies, indica and japonica. Large-scale virulence testing was conducted to evaluate the diversity of pathogenicity for Xoo. We found rapid virulence dynamics against rice, and its determinant factors included the genetic background of Xoo, rice resistance genes, and planting environment of rice. Genetic background was investigated by comparative genomics, which indicated that transposition events contributed the most to evolution of the Xoo genome and the rapid diversification of virulence. This study provided a good model to understand the evolution and dynamics of plant pathogens in the context of interactions with their hosts. Such interactions are influenced by both geographical conditions and farming practices.